FOOTBALL GAME CONCEPTION AND TRAINING FOR THE EIGHTH GRADERS OF THE SPORTS HIGH SCHOOL OF BAC?U - ROMANIA (Fiep Bulletin - online, 2019)
This research aims to create a model of the football game conception and training for the eighth graders of the SportsHigh-School of Bac?u, Romania2.The correct direction of the training process by applying specific training models created by the coach based on thegame conception of his/her own team leads to better athletic results.1.The correct choice of a game conception for the team, based on its players' physical, mental, and technical-tacticalskills, leads to an increase in their ability to play, and, implicitly, to an improvement of the team.The training of young football players in a sports school, starting with the moment of their selection (6-8 years old) anduntil graduation (17-18 years old) takes place over the course of 10-12 years. This period, logically, should be divided into stages.The stage training system creates favorable conditions for a gradual and consecutive training of young football players, as well asfor perfecting their talent. Starting from this context this paper will try to demonstrate that a specific training model for perfecting a game andtraining conception for U15 juniors is formed in correlation with and dependence on the conception of the Romanian FootballFederation, the tradition and regulations of the club, the conception on football of the coach and players. The subjects of this research were eighth graders (U15 juniors) of the Sports High School of Bac?u. The experimentwas conducted between March and June, 2018, on the U15 junior team of the Sports High School of Bac?u. The specific football action means were conceived and conducted within the allocated time of the training lesson of 90minutes. The experiment consisted of an initial testing (March 2, 2018), comprising control challenges, obtaining initial data forthe experiment, two intermediary tests (March 30 and April 26, 2018), and a final testing (May 29, 2018), at the end of theexperiment, through which the final data of the experiment was recorded, using the same challenges. Between the initial and the final testing, the established training means and programs were applied. Throughout theexperiment, the progress of the subjects was recorded using scoring systems that these authors have created for the threefactors: technical, physical, and tactical. At the end of the experiment and after analyzing the recorded results, it can be said that by correctly establishing aspecific training model for the perfecting of game and training conception of U15 junior players, presented in this paper, one wouldensure an increase in the game skills of the players and implicitly of the team.